THU0290 Efficacy and Safety of Tocilizumab in Eight Patients with Takayasu Arteritis. (9th June 2015) - Palmou-Fontana, N.; Loricera, J.; Blanco, R.; Hernández, J.L.; Castañeda, S.; Humbría, A.; Ortego, N.; Bravo, B.; Freire, M.; Melchor, S.; Mínguez, M.; Salvatierra, J.; et al.
Abstract : Background: Takayasu arteritis (TA) is often refractory to corticosteroids and traditional immunosuppressive agents. Interleukin (IL)-6 plays an important role in the pathogenesis of TA. Tocilizumab (TCZ) is a humanized monoclonal anti-IL6 receptor (IL-6R) antibody. Objectives: Our aim was to assess the efficacy of TCZ in patients with TA refractory to conventional treatment. Methods: Retrospective multicenter study of 8 patients treated with TCZ and diagnosed with TA refractory to conventional therapy. We assessed its efficacy (clinical and laboratory parameters) and the reduction in the corticosteroid dose, as well as its side effects. Comparisons were performed between baseline and 1st, 3rd, 6th and 12th months, by means of Wilcoxon's signed rank test. Results: We analyzed 8 patients (all women), mean age, 34±16 years. The main clinical features at TCZ onset were: constitutional symptoms (n=4), fever (n=3), headache (n=2), chest pain (n=1), abdominal pain (n=1), mesenteric ischemia (n=1), lower limbs myalgia (n=1), cerebrovascular insufficiency (n=1), upper limb claudication (n=1) and nodular scleritis (n=1). Before TCZ onset, all patients had received corticosteroids, and 7 of them were also on several traditional immunosuppressive agents: MTX (n=5), cyclophosphamide (n=2), azathioprine (n=2), mycophenolate mofetil (n=2) and cyclosporine A (n=1). Furthermore, 5 of 8 patients were also treated with anti-TNF-α drugs: infliximab (n=4), adalimumab (n=2) and etanercept (n=1). Two of them needed a double switching. TCZ dose ranged between 6-8 mg/kg every 2-4 weeks. TCZ was prescribed as monotherapy in 4 patients or combined with other traditional immunosuppressive agents in other 4. Most of the patients achieved a rapid improvement of clinical manifestations and acute phase reactants after TCZ onset (Table ). Thus, after a mean follow-up of 16±6 months, the median value [IQR] of CRP decreased from 3.09 [0.5-12] to 0.15 [0.1-0.5] mg/dL (p=0.018), ESR dropped from 40 [28-72] to 3 [2-5] mm/1st h (p=0.012) and the prednisone dose was tapered from 42.5 [25-50] to 2.5 [0-7.5] mg/day (p=0.011). One patient developed a systemic lupus erythematosus and discontinued TCZ therapy, and in another one, TCZ was withdrawn due to inefficiency. Other patient had to reduce the dose due to thrombocytopenia. Conclusions: In this multicenter study, TCZ seems relatively effective and safe in patients with refractory TA. However, these preliminary results need to be confirmed in controlled randomized prospective studies. Acknowledgements: This study was supported by a grant from "Fondo de Investigaciones Sanitarias" PI12/00193 (Spain). This work was also partially supported by RETICS Programs, RD08/0075 (RIER) and RD12/0009/0013 from "Instituto de Salud Carlos III" (ISCIII) (Spain). Disclosure of Interest: None declared